2017
DOI: 10.1155/2017/2359389
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Abnormalities Associated with the Metabolic Syndrome by Spinacia oleracea (Spinach) Consumption and Aerobic Exercise in Rats

Abstract: The present study evaluates the protective effects of an antioxidant-rich extract of Spinacea oleracea (NAOE) in abnormalities associated with the metabolic syndrome (MetS) in rats. HPTLC of NAOE revealed the presence of 13 total antioxidants, 14 flavonoids, and 10 phenolic acids. Rats administered with fructose (20% w/v) in drinking water for 45 days to induce abnormalities of MetS received NAOE (200 and 400 mg/kg, po), the standard drug gemfibrozil (60 mg/kg, po), aerobic exercise (AE), and a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…Spinach (Spinacia oleracea L.) is a leafy vegetable crop which is widely cultivated throughout the Mediterranean basin in open-field and protected conditions. It is a common ingredient of many dishes and food products due to the exceptional nutritional value and the important bioactive properties of its leaves [31][32][33]. Apart from beneficial compounds content, spinach may be also rich in antinutrients such as nitrates and oxalates with severe implications on human health that have to be considered, and proper cultivation practices are usually applied to limit the content of such compounds [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Spinach (Spinacia oleracea L.) is a leafy vegetable crop which is widely cultivated throughout the Mediterranean basin in open-field and protected conditions. It is a common ingredient of many dishes and food products due to the exceptional nutritional value and the important bioactive properties of its leaves [31][32][33]. Apart from beneficial compounds content, spinach may be also rich in antinutrients such as nitrates and oxalates with severe implications on human health that have to be considered, and proper cultivation practices are usually applied to limit the content of such compounds [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The dose of 400 mg kg −1 was based on the two studies by Panda et al . The benefits of 14 and 45 days supplementation with HES (400 mg kg −1 ) were reported in these studies …”
Section: Methodsmentioning
confidence: 64%
“…In line with the results of our study, they reported a significant improvement in glucose and lipid profile after 45 days' supplementation. The greatest improvement was observed when spinach extract was accompanied by aerobic exercise . In another study, a 100‐day treatment with spinach thylakoids in female apolipoprotein E‐deficient mice reduced food intake, body weight, serum glucose, triglyceride, and fatty acid compared to the control .…”
Section: Discussionmentioning
confidence: 96%
“…In one study, consumption of spinach powder (%5 of diet) for 6 weeks increased SOD activity in liver of the rats (43). Panda et al showed that 200 and 400 mg/kg HES for 45 days in rats, as part of a high-fructose diet, enhances the activity of SOD and GPx in heart (44). In a clinical trial, Bohlooli et al evaluated the effects of spinach supplementation on antioxidant status and muscle injury in marathon runners.…”
Section: Discussionmentioning
confidence: 99%
“…Random numbers were generated using online random number generators. The dosage of 400mg/kg was based on the two studies by Panda et al which reported the benefits of 14 and 45 days supplementation with HES (400mg/kg) (31,32).…”
Section: Animals and Experimental Methodsmentioning
confidence: 99%